Comment on “Five centuries of cod catches in eastern Canada,” by Schijns et al - Holm, Poul; Hayes, Patrick W; Nicholls, John (ICES journal of marine science, 2022)
Abstract Schijns et al. use a historical time series to inform a stock assessment model for the northern Atlantic cod (Gadus morhua) fishery from 1508 to 2019. They find that catches from the sixteenth century to the 1950s did not exceed 200000 t per annum and could have been sustained today “if fishing effort and mortality had been stabilized in the 1980s”. Had Schijns et al. used a more complete and representative time series (as identified below), they would have found that catches were substantially higher during much of the time period, possibly affecting their conclusions regarding the timing and onset of unsustainable exploitation. In an earlier paper, based on original archival documentation, we have argued that total landings in the Newfoundland fishery averaged 400000 t in the eighteenth century and peaked at 600000 t in 1788. We contend that pre-industrial technology was sufficient to have a significant impact on marine life.